An application of geomarketing to coastal tourism areas - María Pilar Peñarubia-Zaragoza; Moisés Simancas-Cruz; Geraldine Forgione-Martín (Tourism & Management Studies)
Geomarketing allows geographical units to be defined with a certain degree of homogeneity in terms of tourists’ preferences, behaviours, needs, expectations, purchase and consumption patterns and analogous attitudes. The result is a ‘territorial segmentation’ of tourists’ demands in accordance with tourism areas’ geographical characteristics. This study sought to examine the benefits and disadvantages of applying geomarketing to territorial segmentation of demand in coastal tourism areas. An empirical analysis was conducted of data on tourist accommodation establishments specialising in family tourism in Costa Adeje, Spain. The findings include that the tourist accommodation variable is essential to any successful segmentation process, including the micro-segmentation of coastal tourism areas. This variable facilitates the grouping of consumers with similar demands in a market based on shared needs, habits or attitudes and, from the supply side, on areas’ characteristics. The latter territorial aspects are crucial to public and private decision-making processes. Thus, geomarketing is an ideal technique for understanding tourists.